Analisis Kemampuan Klasifikasi Berbasis Objek untuk Pemetaan Perubahan Penutup Lahan Menggunakan Citra Landsat 8 di Kabupaten Jember Bagian Timur - Era Iswara Pangastuti; Elan Artono Nurdin; Yushardi Yushardi; Fahmi Arif Kurnianto (Universitas Lambung Mangkurat, 2022)
Land is a complex system that requires good management. Along with population growth, it will result in an impact of increasing both the quality and quantity of life necessities that can change land use. This research is deemed necessary to make an interpretation using remote sensing. The use of remote sensing (PJ) is very important in presenting spatial information related to the appearance of an area. The purpose of this study is to assess the accuracy and analyze object-based classification for mapping land use change in parts of Jember Regency using Landsat 8 imagery. The method is used in this study uses Object Based Image Analysis (OBIA), optimal box classifier for the classification process, visual interpretation. segmentation results to classify land use changes. Based on the results of the land use / cover classification capability test in Kaliwates, Sumbersari, Pakusari, Mayang and Silo Districts using the OBIA method, it shows an accuracy value of 94.28% for Landsat 8 images recorded in 2015, and an accuracy value of 98.57% for images. Landsat 8 recording for 2020.